Proverbs and Foreign language teaching - Alidjanova Nodira Murodilloyevna (Zien Journals, 2022)
this article investigates the importance of proverbs in teaching foreign languages. It shows that proverbs play an important role in language teaching, getting cultural knowledge, figurative comprehension and communicating skills. It gives definition to the proverb and explains what it is, reveals how it is used in teaching and learning process of foreign language.
Keywords: Proverb; Phraseology; Figurative Meaning; Communication